The Role of Cell Block in Diagnosing Metastatic Adenocarcinoma in Pleural Fluid: A Case Series - Salsa Hanisa Anwar Salsa Hanisa; Desi Puspita Desi; Hermin Aminah Usman Hermin Aminah (Frontiers on Healthcare Research, 2026)
Background: Cytological examination of pleural fluid is an important, inexpensive, and simple test for detecting malignancy in patients with clinical pleural effusion who undergo thoracentesis. Adenocarcinoma is the most common tumor type. However, diagnosis using the conventional smear method can be challenging when the typical glandular-like growth patterns are not visible. Cell block preparation from pleural fluid samples preserves tissue architecture and tumor cell genetic material, enabling further tests such as immunohistochemistry (IHC) and PCR. Case presentation: We report a series of four patients with pleural effusion who underwent both conventional smear cytology and cell block examination. Tumor cell growth patterns were identified and descriptively analyzed for each sample. In two of these cases, vague glandular-like growth patterns were observed only in the cell block preparations and were absent in the conventional smears, which directly helped establish the diagnosis of metastatic adenocarcinoma. Conclusion: Differences in tumor cell growth patterns between the conventional smears and the cell block preparations were observed in two cases. The vague glandular-like growth pattern that was present in the cell block but was not identified in the conventional smear aided pathologists in identifying metastatic adenocarcinoma in pleural fluid specimens.